PKM Edukasi Kewargaan Damai melalui Penguatan Literasi Digital dan Literasi Kebangsaan di SMK Telkom Makassar - Andi Aco Agus; M. Yunasri Ridhoh; Randiawan Randiawan; Amirullah Amirullah; Ilham Samudra Sanur (Universitas Negeri Makassar, 2026)
The development of digital technology has significantly transformed communication patterns, social interactions, and the way young people access information. On the one hand, these developments provide great opportunities to improve knowledge access and civic participation. On the other hand, the rapid flow of information also creates challenges such as the spread of hoaxes, hate speech, intolerance, and low digital ethics among students. This condition highlights the importance of strengthening digital literacy alongside national literacy so that students can become critical, responsible citizens oriented toward peaceful values. This Community Service Program was conducted at SMK Telkom Makassar with the aim of improving students’ understanding of digital literacy, national literacy, and peaceful citizenship. The implementation methods included socialization, training, participatory discussions, case simulations, and mentoring sessions. The results showed an increase in participants’ understanding of wise digital media use, the importance of maintaining unity in digital spaces, and the ability to respond to differences peacefully and tolerantly. The program also encouraged students to become agents of change in creating a healthy school environment and social media culture. Therefore, this community service activity contributed positively to building democratic, inclusive, and peace-oriented digital citizenship character.